1999
DOI: 10.1017/s0031182099004370
|View full text |Cite
|
Sign up to set email alerts
|

The systemic immune response of BALB/c mice infected with larval Taenia crassiceps is a mixed Th1/Th2-type response

Abstract: The subsets of lymphocytes and cytokines regulating the site-specific immune response in experimental cysticercosis (Taenia crassiceps) are not known. This study investigated the cells present at the site of infection (PECs) using flow cytometry and measured the cytokines produced by these cells through 50 days of infection. The results showed an expansion of B220+CD5+, B220+CD5-, alpha beta TCR+CD4+ and CD8+ cells coincident with a transient increase in IL-10 production. After the initial increase, the percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
42
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 21 publications
3
42
0
4
Order By: Relevance
“…Although it is widely accepted that Th2-like response mediates protective immunity against most helminths (5), its role in mediating protection against murine cysticercosis is not clear (6).…”
mentioning
confidence: 99%
“…Although it is widely accepted that Th2-like response mediates protective immunity against most helminths (5), its role in mediating protection against murine cysticercosis is not clear (6).…”
mentioning
confidence: 99%
“…Soon afterwards there is a strong Th2 polarization due to the immunoregulatory capacity of the parasite increasing serum levels of IgG and IgE as well as IL-4, IL-13 and IL-5, which inhibits the initial Th1 response and favors the growth of parasitic burden 7,8,10,11 . The experimental models exploring the neurological location of cysticerci are described using Mesocestoides corti 5,12,13 and T. crassiceps 6 . The model carried out with M. corti was used to describe the role of defense cells and cytokines in the host-parasite relationship 13 , the expression of Toll-like receptors 5 , the migration of leucocytes to the central nervous system, the junction complex proteins and the immune system evasion strategies 14 .…”
mentioning
confidence: 99%
“…There are only few studies available regarding aspects of the cellular immune response, most of them showing immunosuppression in humans 4 , pigs 5 , and in experimental mouse models [6][7][8][9] . A study from our group using a lymphoproliferation assay with T. solium and T. crassiceps antigens as stimuli showed an antigen-specific suppression in NC-patients, suggesting that the antigenic components play a suppressor role in the host immune response 10 .…”
mentioning
confidence: 99%
“…The immunosuppression observed in experimental cysticercosis seems to be related to the cytokine profile 8,[13][14][15] . Our contribution in this field showed that by using T. solium antigen as stimuli, there is a predominance of Th1 response in inflammatory NC-patients and a mixed Th1/Th2 pattern in noninflammatory NC-patients 12 .…”
mentioning
confidence: 99%
See 1 more Smart Citation